The Impact of Non-Physical Bullying on Adolescents' Self-Concept: An Observational Study in the Adolescent Community in Sausapor, Tambrauw Regency, West Papua, Indonesia - Tamaela, Josepha Mariana; Nurhidayah Amir; Mariyo Jane Sanggel; Rifki Sakinah Nompo (HM Publisher, 2024)
Introduction: Non-physical bullying, often subtle and insidious, poses a significant threat to adolescents' self-concept during a critical developmental period. This study investigates the prevalence and impact of non-physical bullying on adolescents' self-concept within the unique cultural context of Sausapor, Tambrauw Regency, West Papua, Indonesia. Methods: A cross-sectional observational study was conducted among adolescents aged 12-17 years in Sausapor. Data were collected using validated questionnaires assessing non-physical bullying experiences and self-concept dimensions (self-esteem, self-efficacy, and body image). Descriptive statistics, chi-square tests, and regression analyses were employed to examine the relationship between non-physical bullying and self-concept. Results: The study revealed a significant prevalence of non-physical bullying in the Sausapor adolescent community, with verbal abuse and social exclusion being the most common forms. Non-physical bullying was significantly associated with lower self-esteem, reduced self-efficacy, and negative body image among adolescents. Regression analyses confirmed the detrimental impact of non-physical bullying on self-concept, even after controlling for sociodemographic factors. Conclusion: Non-physical bullying is a pervasive issue in Sausapor, with profound negative consequences for adolescents’ self-concept. Culturally sensitive interventions are urgently needed to prevent and address non-physical bullying, promote positive self-concept development, and foster a supportive environment for adolescents in this community.